Community-based approach for dengue prevention and control in Sta. Cruz, Laguna, Philippines - Carandang, Rogie Royce; Valones, Ariel; Valderama, Maria Theresa; Cotoco, Karla; Asis, Edward (International Journal Of Community Medicine And Public Health, 2017)
Background: Despite having mandated health programs, dengue cases in Sta. Cruz had a marked increase of 106% in the past two years. Dengue ranked first on notifiable diseases in Sta. Cruz with a rate of 520 per 100000 populations. The occurrence of dengue in one barangay is a threat to nearby barangays and its spread intensified due to proliferating trade and travel. Therefore, dengue cannot be controlled if efforts are limited to only a few members of the community. Hence, strengthening the implementation of dengue programs must be pointed out. Methods: The community project aims to decrease the incidence of dengue cases in all the barangays of Sta. Cruz by 30% within one year. The strategic plan is designed that a Core Group has to be made in which the capacity of staff at different levels has to be increased. An assessment of their baseline knowledge, post-test results, return demonstration and field implementation was conducted. Strengthening communication for source reduction was made possible by posting dengue posters in conspicuous places and by sustained advertising of dengue jingle. Results:The Dengue-Rous Core Group acquired the knowledge, skills and capacity to deliver effective dengue prevention at the community level. The awareness and capacity building of each household to regularly practice search and destroy of mosquito breeding and resting places in their community were also enhanced. Conclusions:Our findings highlight the need for further information, education and communication on source reduction of mosquitoes. Identifying barriers to action and to seek ways to translate population knowledge about dengue into positive preventive practices are deemed essential.